Transcutaneous Electrical Cranial-Auricular Acupoint Stimulation vs. Escitalopram for Patients With Mild-to-Moderate Depression (TECAS): Study Design for a Randomized Controlled, Non-inferiority Trial - Yang, Sichang; Qin, Zongshi; Yang, Xinjing; Chan, Mei Yan; Zhang, Shuiyan; Rong, Peijing; Hou, Xiaobing; Jin, Guixing; Xu, Fengquan; Liu, Yong; Zhang, Zhang-Jin (Frontiers in Psychiatry, 2022)
Background Previous studies in animals and humans indicated that transcutaneous vagus nerve stimulation (tVNS) and transcutaneous electrical acupoint stimulation (TEAS) on trigeminal nerve-innervated forehead acupoints can relief the symptoms of depression. However, due to the limited investigations on these two interventions, more research are needed to confirm their efficacy in depression. To improve the efficacy of the single treatment, we combined two treatments and created a novel non-invasive stimulation, transcutaneous electrical cranial-auricular acupoint stimulation (TECAS). To assess the efficacy and safety of TECAS, we compare it with a selective serotonin reuptake inhibitor (SSRI), escitalopram, for the treatment of depression. Methods/Design This is a multi-center, non-inferiority, randomized controlled trial that will involve 470 patients with mild to moderate depression. Patients will be randomly assigned to either the TECAS group or the escitalopram group in a 1:1 ratio. The TEAS group will receive two sessions of treatments per day for 8 consecutive weeks, and the escitalopram group will receive 8 weeks of oral escitalopram tablets prescribed by clinical psychiatrists as appropriate for their condition. The primary outcome is the clinical response as determined by Montgomery-Åsberg Depression Rating Scale (MADRS) scores at week 8, with −10% as the non-inferior margin. The secondary outcomes include the response rate determined by 17-item Hamilton Depression Rating Scale (HAMD-17), remission rate, changes from baseline in the scores on the MADRS, the HAMD-17, the Hamilton Anxiety Rating Scale (HAMA), the Pittsburgh Sleep Quality Index (PSQI), and the Short Form 36 Health Survey (SF-36). Discussion This will be the first randomized controlled trial to compare the efficacy of TECAS with escitalopram for depression. If effective, this novel intervention could have significant clinical and research implications for patients with depression. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT03909217].